Duration of Oral Contraceptives Use and Risk of Development of Dyslipidemia among Women in Dhaka City (Journal of Science Foundation, 2017)
AbstractBackground: Duration of oral contraceptive use is an important issue for the development of dyslipidemia among women.Objective: The purpose of the present study was to see the duration of use of OCP and the development of dyslipidemia among the women.Methodology: This case control study was carried out in the Department of Obstetrics & Gynaecology and Family Planning Department in collaboration with the Biochemistry Department at Sir Salimullah Medical College & Mitford Hospital, Dhaka from June 2009 to May 2010 for a period of one (1) year. Women using low-dose OC pill for more than one year were considered as cases group while women not using low-dose oral contraceptive pill were taken as control group of the study. Lipid profiles were performed in the laboratory in the fasting state from blood.Result: A total of 80 subjects were recruited for this study of which 40 women in case group and the rest 40 women were in control group. Duration of contraceptive use and serum lipids profiles were recorded. Level of serum total cholesterol, serum triglyceride, and serum LDL were significantly higher among the contraceptive users of > 5 years duration than those among 5 or < 5 years duration (p < 0.001). However, serum HDL level was low among both users and non-users (p=0.556). The risk of developing dyslipidaemia in women using low-dose oral contraceptive was more than 3-fold higher than that in non-users.Conclusion: In conclusion the greater the duration of oral contraceptive use the higher is the chance of dyslipidaemia.Journal of Science Foundation 2016;14(2):40-43